FORMULATION OF NANOEMULSIONS FROM CERBERA ODOLLAM SEEDS ESSENTIAL OIL AND THEIR LARVICIDAL ACTIVITIES AGAINST AEDES AEGYPTI LARVAE - Azlan bin Kamari (Tanjung Malim, 2024)
FORMULATION OF NANOEMULSIONS FROM CERBERA ODOLLAM SEEDS ESSENTIAL OIL AND THEIR LARVICIDAL ACTIVITIES AGAINST AEDES AEGYPTI LARVAE by Azlan bin Kamari